To observe the intensity of the inflammatory reaction caused by neonatal urine and meconium on the intestinal wall of rats in order to understand etiology of intestinal damage in gastroschisis - Samala, Devdas S. (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVES: The aim of this experimental study was to observe the intensity of the inflammatory reaction caused by neonatal urine and meconium on the intestinal wall of rats to better understand etiology of intestinal damage in gastroschisis. MATERIALS AND METHODS: A total of 24 adult Wistar rats were used as experimental models to simulate the effect of exposed bowel in cases of gastroschisis. The peritoneal cavity of the rats was injected with substances which constitute human amniotic fluid to study the effect on the bowel. Sterile urine and meconium were obtained from newborn humans. The rats were divided into four groups according to the material to be injected. In Group I (Control group) 3 mL of distilled water was injected, in Group II (Urine group) 3 mL of neonatal urine was injected, in Group III (Meconium group) 5% meconium suspension was injected, while in Group IV, a combination of 5% meconium suspension and urine was injected. A total of 3mL solution was injected into the right inferior quadrant twice a day for 5 days. The animals were sacrificed on the 6(th) day by a high dose of thiopentone sodium. A segment of small bowel specimen was excised, fixed in paraffin, and stained with hematoxylin-eosin for microscopic analysis for determination of the degree of inflammatory reaction in the intestinal wall. All pathology specimens were studied by the same pathologist. RESULTS: The maximum bowel damage was seen in Group II (Urine group) in the form of serositis, severe enteritis, parietal necrosis, and peeling. A lesser degree of damage was observed in Group III (Meconium group) as mild enteritis (mild lymphoid hyperplasia). The least damage was seen in Group IV (Combination of meconium and urine) and Group I (Control group). CONCLUSION: The intraabdominal injection of neonatal human urine produces significant inflammatory reactions in the intestinal wall of rats.